2008
DOI: 10.1111/j.1545-5300.2008.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

How do I Analyze Thee? Let Me Count the Ways: Considering Empathy in Couple Relationships using Self and Partner Ratings

Abstract: In this article we describe some of the benefits and challenges of using self ratings and ratings of the partner to measure empathy and similar terms in couple research. If both members of the dyad are assessed, there will be four measures of the same variable. How to use these 4 measures in research and clinical work is a central question in this paper. We demonstrate 3 different latent models that can be used to analyze these ratings based on different theoretical premises. Using empathy as the independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 41 publications
4
57
0
1
Order By: Relevance
“…First, because the study was cross-sectional, we cannot establish the direction of influence underlying the associations between empathy and relationship satisfaction. However, there is supporting evidence from other longitudinal research that empathy does indeed influence relationship satisfaction a year later, even when controlling for satisfaction levels in the prior year (Busby & Gardner, 2008). Thus, there is empirical grounding for examining the association between empathic processes and relationship satisfaction in the direction that we pursued in this study.…”
Section: Empathic Accuracy and Relationship Satisfactionmentioning
confidence: 83%
See 1 more Smart Citation
“…First, because the study was cross-sectional, we cannot establish the direction of influence underlying the associations between empathy and relationship satisfaction. However, there is supporting evidence from other longitudinal research that empathy does indeed influence relationship satisfaction a year later, even when controlling for satisfaction levels in the prior year (Busby & Gardner, 2008). Thus, there is empirical grounding for examining the association between empathic processes and relationship satisfaction in the direction that we pursued in this study.…”
Section: Empathic Accuracy and Relationship Satisfactionmentioning
confidence: 83%
“…One study showed that perceptions of empathy are a stronger predictor of women's satisfaction than men's a year later, even when controlling for their baseline levels of satisfaction, and it was the man's empathy variables that had the greatest influence on both hers and his satisfaction (Busby & Gardner, 2008). So, while the male's views and actions in regard to empathy are stronger predictors of relationship quality over time, it is the female's satisfaction and relationship well-being that are more strongly affected.…”
Section: Current Studymentioning
confidence: 99%
“…Thus, we also examine the possible effects of listening to a friend's story of stress. Hearing about a friend's troubles may have benefits for the conversational partner, as research shows that empathic responses can result in positive perceptions of the listener's competence (Jones, 2004), as well as increases in relational satisfaction over time (Busby & Gardner, 2008). However, listening to stories of difficulty, particularly over time, could be mildly upsetting to friends if the storytelling results in emotional contagion, burn-out, excessive co-rumination (Rose, 2002), or the listener feeling ineffectual, frustrated, or imposed upon (Goldsmith, 2004).…”
mentioning
confidence: 99%
“…A relação consistente entre o IRIC, enquanto medida de empatia expressa no contexto da relação de casal, e a satisfação e estabilidade conjugal, salienta o papel que ambas as dimensões avaliadas pelo IRIC (empatia cognitiva e emocional), desempenham no ajustamento e satisfação do casal (Davis & Oathout, 1987). Essa relação comprova a relevância clínica do uso desse instrumento em contextos clínicos e é consistente com os resultados de outros autores (Busby & Gardner, 2008;Davis & Oathout, 1987;Long & Andrews, 1990;Long, Angera, Carter, Nakamoto, & Kalso, 1999). Outros estudos encontraram também relação da empatia diádica com outras variáveis de ajustamento relacional, tais como satisfação sexual (Larson, Anderson, Holman, & Niemann, 1998) ou perdão após a transgressão do parceiro (Fincham, Paleari, & Regalia, 2002).…”
Section: Discussionunclassified